PENGENDALIAN KUALITAS PRODUKSI BENANG PARTIALLY ORIENTED YARN DENGAN MENGGUNAKAN METODE SEVEN TOOLS (Studi Kasus Departemen POY CP-3 PT. Indorama Synthetics Purwakarta Tbk) - Puspita, Khairina; Daisy Ade Riany Diem; Sutarjo (Jurnal Teknologika, 2023)
. PT Indorama Synthetics Purwakarta Tbk, located on Jl. Industri Ubrug kembangkuning, Kec. Babakan Cikao, Purwakarta Regency is engaged in textile, namely in terms of spinning and polyester, rayon yarn, recycled polyester yarn and blended yarn from synthetic fiber and recycled fiber. This study aims to determine the types of defects that are dominant in POY-CP3 yarn products, determine the factors that cause defects in POY CP-3 yarn products, find out how to control quality in order to reduce the amount of damage or defects in POY CP-3 yarn. In this study, the authors used data on the number of yarn defects for the period April 2022 to April 2023. This research uses seven tools in the form of flow charts, cheek sheets, histograms, scatter diagrams, pareto diagrams, cause-and-effect diagrams, and control maps. Based on the results of the research analysis, it can be concluded that although there are still defective products, the company has carried out quality monitoring starting from quality control of raw materials, process quality control. From the calculation data with C-Chart analysis that yarn defective products in April 2022 to April 2023 are outside the control limits (out of control). With product damage that is outside the control limits or out of control, the company must better maintain the production process so that damage does not occur outside the control limits. So that the production produced in the next period can meet the quality standards.